Design and implementation of solar-powered with IoT-Enabled portable irrigation system - Roshahliza, M. Ramli; Jabbar, Waheb A. (KeAi Communications Co., 2022)
This paper proposes a solar-powered portable water pump (SPWP) for IoT-enabled smart irrigation system (IoT-SIS). A NodeMCU microcontroller with a Wi-Fi interface and soil moisture, temperature, and humidity sensors are exploited to monitor and control the water pump and build an IoT-based irrigation system. The proposed irrigation system updates the gathered information from sensors (moisture, temperature, and humidity) using an integrated algorithm to the Blynk IoT cloud in real-time. Farmers can access this information and control the water pump accordingly via a user-friendly interface using their smartphones. The portable and eco-friendly water pump is powered via a solar panel and can be controlled using Blynk mobile application, which is also used to monitor the surroundings. The fabricated pump is inspired by wheeled travel luggage and is equipped with a water filter and multi-nozzles sprayer. The developed solar-based water pump has managed to save electricity and mitigate operational costs. Furthermore, the integration of the IoT concept has facilitated real-time monitoring and control of the pump; thus, enhancing the water usage efficiency and enabling convenient farming operations. The system functionality has been practically tested in a real environment, and its performance has been evaluated.